Effects of long-distance running on the marital relationship - Glazko, Susan (My University, 1986)
A demographic and marital stability (Booth et al., 1983) questionnaire was administered to 242 married adults who ran, or whose spouse ran, 20 miles per wk or more, to determine whether there was a diff in marital stability among couples in which both spouses run, couples in which only the male runs, and couples in which only the female runs. A Kruskal-Wallis One-Way ANOVA was conducted to determine any diff in marital stability among the 3 running groups. Although sig was approached (p=0.0512), the null hypothesis was accepted, thus marital stability was not different among running groups. Since the researcher who developed the Marital Instability Index conducted statistical analysis on each of the 28 questions, a X2 test on each question was also employed. Only 3 questions showed sig (p<0.05), and all involved discussing marital problems with friends, relatives, or counselors. These questions showed sig because the male runner group tended to answer them with more stability, and the runner-couple was less stability. It was concluded that there was no sig diff in marital stability among the runner-couple, the male runner, and the female runner groups.
Keywords: Marriage; Married people; Running -- Physiological aspects